Burden of Peripheral Artery Disease and Its Attributable Risk Factors in 204 Countries and Territories From 1990 to 2019 - Lin, Jinfeng; Chen, Yangbo; Jiang, Nan; Li, Zuoshi; Xu, Shangbo (Frontiers in Cardiovascular Medicine, 2022)
Background Data on burden of peripheral artery disease (PAD) and its attributable risk factors are valuable for policymaking. We aimed to estimate the burden and risk factors for PAD from 1990 to 2019. Methods We extracted the data on prevalence, incidence, death, years lived with disability (YLDs), and years of life lost (YLLs) from the Global Burden of Disease Study 2019 to measure PAD burden. Moreover, the attributable burden to PAD risk factors was also estimated. Results Globally, in 2019, 113,443,017 people lived with PAD and 10,504,092 new cases occurred, resulting in 74,063 deaths, 500,893 YLDs, and 1,035,487 YLLs. The absolute numbers of PAD prevalent and incident cases significantly increased between 1990 and 2019, contrasting with the decline trends in age-standardized prevalence and incidence rates. However, no statistically significant changes were detected in the global age-standardized death or YLL rates. The burden of PAD and its temporal trends varied significantly by location, gender, age group, and social-demographic status. Among all potentially modifiable risk factors, age-standardized PAD deaths worldwide were primarily attributable to high fasting plasma glucose, followed by high systolic blood pressure, tobacco, kidney dysfunction, diet high in sodium, and lead exposure. Conclusion PAD remained a serious public health problem worldwide. More strategies aimed at implementing cost-effective interventions and addressing modifiable risk factors should be carried out, especially in regions with high or increasing burden.